The cycle of public policies for professional and technological education in the state of Rio de Janeiro - Alexandre Batista Dantas; Joel de Lima Pereira Castro Junior; Giuliano Alves Borges Silva (Arizona State University, 2020)
Public policies, especially in the area of professional education, are developed according to the productive order articulated with an institutional configuration, power relations and social practices. In this sense, they tend to express themselves in the processes of vocational training and the level of worker qualification. This article aims to understand the factors that influenced the institution of public policy of professional and technological education in the State of Rio de Janeiro, from conception to contemporary compositions through the theoretical support of policy cycle. Using a qualitative approach to documentary research, historical research, and bibliographic research, the investigation adopts the seven phases of the cycle as a proposal of analytical tool. The data suggest that there are mistakes in the strategies for formulating and implementing the policy, evidenced by the dissociation between the objectives of governmental actors and non-governmental ones, such as in the amount of budgetary resources for maintenance and modernization of existing school units and in the form of provision (competition or contract) of the teaching staff. Some consequences are the reduction in the number of enrollments to the detriment of other networks of technical schools and the low rates of evaluation, thus requiring the redesign of the policy.